MLMI-2024: The dataset of mosquito larvae microscopic images (Aedes aegypti and Culex quinquefasciatus) collected from Surabaya, IndonesiaMendeley Data - Rizka Wakhidatus Sholikah; Afrida Rohmatin Nuriyah; Annisaa Sri Indrawanti (Data in Brief)
Indonesia is a tropical country where mosquitoes are common. There are >100 species of mosquitoes found in Indonesia. Some of these species can carry diseases such as dengue fever, which is caused by the Aedes aegypti mosquito, and West Nile virus, which is carried by the Culex quinquefasciatus mosquito. Mosquito larvae are found in stagnant or slow-moving water, and identifying the species of larvae is important in medical and veterinary entomology to determine the potential risk of disease. The dataset includes two species of mosquito larvae: Aedes aegypti and Culex quinquefasciatus, which are divided into four parts: head, abdomen-8, siphon, and full body. This dataset can be useful for medical entomologists to classify mosquito larvae quickly and automatically.